Imaging features of giant sialolith of submandibular gland: A case report - Komalpreet Kaur; Aravinda Konidena; Gagan Puri; Deepa Jatti (Wolters Kluwer Medknow Publications, 2016)
Sialolithiasis is an obstructive salivary disease due to salivary stone formation, also known as "meal time syndrome" because of its association with meal times, usually measuring less than 1 cm. However, occasionally giant sialoliths as large as 3 cm have been reported. Here, we report an interesting case of large intraductal sialolith of submandibular salivary gland in an old patient, with relevant radiological investigations and review of literature.